“The Poor will always be with you”: Ethical Implications for the Church and Development in Africa. - Rugyendo, Medard (Kabale University, 2024)
We live in the world and Africa in particular where the Church promotes the love of God and neighbor but also harbours the poor as well. However, in the gospels, Jesus in Matthew 26:11 echoed the words of Deuteronomy 15: 11 that the “poor will always be with you” when a woman poured expensive oil on him preparing him for his death. To most people, it is believed that he meant that poverty is unstoppable, unbreakable, unavoidable, and predetermined by God yet it is created by human beings when they disobey God and neglect their neighbor. Christians ought to help each other and witness justice through sharing, clothing and providing shelter for the poor. This paper seeks to delve into the meaning of Jesus’ words and propose ethical implications for Christians. What’s the role of Christians in fighting poverty amongst themselves? Is poverty unavoidable? Is it predetermined by God? Through biblical search and other thinkers, the meaning and implications will be drawn.